Liquid chromatography and mass spectrometry for the analysis of acylglycerols in art and archeology. Issue 4 (9th July 2020) - La Nasa, Jacopo; Modugno, Francesca; Degano, Ilaria
Abstract : Lipid characterization in art and archeology, together with the study of lipid degradation processes, is an important research area in heritage science. Lipid‐based materials have been used as food since ancient times, but also employed as illuminants and as ingredients in cosmetic, ritual, and pharmaceutical preparations. Both animal and plant lipids have also been processed to produce materials used in art and crafts, such as paint binders, varnishes, waterproofing agents, and coatings. Identifying the origin of the lipid materials is challenging when they are found in association with artistic historical objects. This is due to the inherent complex composition of lipids, their widespread occurrence, and the chemical alterations induced by ageing. The most common approach for lipid characterization in heritage objects entails profiling fatty acids by gas chromatography/mass spectrometry after saponification or transesterification. New developments in high‐performance liquid chromatography coupled with mass spectrometry (HPLC‐MS) for the characterization of acylglycerols, together with more efficient sample treatments, have fostered the introduction of liquid chromatography for characterizing the lipid profile in heritage objects. This review reports the latest developments and applications of HPLC‐MS for the characterization of lipid materials in the field of heritage science. We describe the various approaches for sample pretreatment and highlight the advantages and limitations of HPLC‐MS in the analysis of paint and archeological samples. © 2020 John Wiley & Sons Ltd.